Representational Models and Democratic Transitions in Fragile and Post-Conflict States - Goldstone, Jack A. (Washington, DC: World Bank, 2012)
Proposes that poor pre-industrial countries, including those just recovering from or even struggling with violent conflicts, should be encouraged and aided in quickly setting up democratic institutions.Following the fall of the Soviet Union, building democracy in war-torn and corrupt states has offered hope for addressing key problems such as corruption and ineffectiveness.For practical purposes, democracy assistance has generally taken a two-part approach: (1) holding free and fair elections and (2) developing the broader functional perquisites of democracy, including a strong civil society, rule of law, political equality, fighting corruption, and provision of essential education, health, and infrastructure. Two particularly important issues that domestic and international democracy reformers face: the timing or sequencing of elections in relation to other political and social changes, and the choice made among different electoral and representation systems.